Implementation of Online Teaching During the Covid-19 Pandemic: Teachers’ Experiences - Rintani Hidayat; Kastam Syamsi (STAI Hubbulwathan Duri, 2022)
This study aims to analyze the learning process online, how is the level of readiness of teachers in organizing online learning, how is the level of readiness of students in receiving online learning. The supporting factors and inhibiting in implementing the courage system learning daring the COVID-19 pandemic. This study was conducted at one of Senior Hight School in Merangin. This research is qualitative. The data subjects in the study were all Indonesian language teachers at Senior Hight School in Merangin totaling six teachers. The data collection techniques in this study were in the form of observation and interviews. The collected data is then processed and analyzed to be presented in the form of narrative paragraphs. The data analysis process begins with data reduction, data analysis, interpretation, and conclusion. The results of this study reveal that online learning has been carried out quite well by Indonesian language teachers during the COVID-19 pandemic. This is because the teacher has prepared lesson plans, learning activities, and learning evaluations. The benefits of online learning that most teachers feel are increased competence in using technology for learning. Teachers’ adaptations to the implementation of online learning during the COVID-19 pandemic include gathering information to increase their understanding of online learning through internet media such as Google and YouTube. However, online learning has constraints in the implementation of which is unstable tissue conditions and learners’ difficulties in understanding learning materials are unique challenges in online learning.